The second-order adjoint sensitivity analysis methodology - Cacuci, Dan Gabriel (Advances in applied mathematics., 2018)
"The author has achieved the breakthrough of generalizing the First-Order Theory presented in his previous books, to the efficient computations of arbitrarily high-order sensitivities for nonlinear systems (HONASAP). This breakthrough has many applications, especially when there is a need to quantify nonlinear behavior or to quantify uncertainties in design parameter/system responses in large-scale systems. This book presents the theory of the HONASAP with applications, from simple, analytically solvable, paradigm problems to large-scale applications in thermal hydraulics, particle transport, etc."--Provided by publisher